Lower extremity injury evaluation an interactive approach - Wiksten, Denise L., 1965-; Barry, Brian, M.A. (Thorofare, NJ : SLACK, 2001)
(Producer) In this CD-ROM, three dimensional anatomical models allow one to take a virtual reality tour of pertinent anatomy and view models from all angles. Organized in the following areas: thoracic spine, lumbar spine, pelvic and sacral, hip and groin, knee, and ankle
System requirements: Pentium 100 or faster processor; Microsoft Windows 95 or later; 16 MB RAM, 1 MB (or higher) SVGA video card; 2X CD-ROM drive; 8-bit Sound Blaster-compatible sd. card; Quick Time 4.0 or higher for Windows (included)
System requirements: Power PC processor; Mac OS version 7.5 or later; 2X CDROM drive; 16 MB of RAM; Quick Time 4.0 or higher for Macintosh (included)
Keywords: Leg Injuries -- diagnosis; Leg -- anatomy & histology